Produtividade e qualidade da silagem de sorgo de diferentes híbridos na região sudoeste do Paraná - Vargas, Marcelo Pronobi de (2021)
Silage is a way to store forage of similar quality to a fresh plant and to provide it in periods that have a low forage production in relation to climatic conditions. The experiment aimed to find the best sorghum hybrid for silage production in the Southwest region of Paraná, seeking good productivity and quality of ensiled material based on biometric and quantitative evaluations of dry and green matter. The hybrids Agri 002E (tall forage hybrid), Maxsilo (sugar hybrid), Qualysilo and Podium (silage hybrids) were evaluated using a completely randomized experimental design (DIC) with four treatments (hybrid evaluation) and four replications, using a total area of 591.25 m2. The identification of the number of days needed to reach 50% of flowering (DFLOR) and number of days to harvest (DCOLH) they was carried out the biometric evaluations of plant height (ALT) and stem diameter (DIAM) were performed before ensiling, when the grains from the center of the panicle reached the milky grain stage. The evaluations of characteristics of the silage, were under the same experimental design, but with 12 repetitions, experimental minisilos that were made with plastic bags of 20 microns with a capacity of 1 kg. The sealing was carried out with the aid of an industrial vacuum packaging machine (model GS620F) five silages were used to determine the aerobic stability and the other five to evaluate the pH, electrical conductivity and water activity. Sowing were carried out the 2020/2021 summer crop in a no-tillage system sown in Mix Rx520 straw. The base fertilization was 527.38 kg/ha of the formula 13-24-12, in coverage 150 kg/ha was applied, divided into two applications in stage V3 and V6. The highest plant heights were found in the hybrids Agri 002E and Maxsilo. Regarding the crop cycle, the Qualysilo hybrid was the earliest and Agri 002E the latest. The production of green matter was higher for the Agri 002E hybrid, followed by the Maxisilo hybrid, which did not differ from Podium. The material with the highest dry matter yield was Agri 002E, without, however, differing from Maxisilo and Podium hybrids. The Qualysilo hybrid produced less dry and green matter. The material that obtained the largest participation of panicles in the plant was in the Qualysilo hybrid, followed by Podium and the smallest participation in the Maxisilo hybrid. The evaluated hybrids showed good productivity and also agronomic characteristics suitable for the production of silage with good fermentation pattern.